Uncle Remus : the complete tales - Lester, Julius, 1939-2018; Pinkney, Jerry (1999)
The tales made famous by Joel Chandler Harris now retold in a "modified contemporary southern black English" that preserves the story line, wit and playfulness and also makes them more accessible today
Bk. 1. The tales of Uncle Remus -- bk. 2. More tales of Uncle Remus -- bk. 3. Further tales of Uncle Remus -- bk. 4. The last tales of Uncle Remus
Includes index
Reprint in one volume of works originally published separately, 1987-1994
Keywords: African Americans -- Folklore; Animals -- Juvenile fiction; Tales -- United States; Fiction